Determination of Agronomical Characters as the Resistance Attributes of Twenty Soybean Varieties to Stink Bug (Nezara viridula L.) - Heru Kuswantoro; I Made Jana Mejaya; Yuliantoro Baliadi (AGRIVITA, Journal of Agricultural Science, 2020)
The research was conducted to study the agronomical characters as the resistance attributes of twenty soybean varieties to Nezara viridula. The results showed that the twenty soybean varieties had a different response to stink bug infestation. Gepak Kuning, Seulawah, and Sinabung were resistant to stink bug, while Argomulyo were highly susceptible, and Grobogan and Malabar were susceptible. Besides resistance to stink bug, Sinabung also had the highest seed yield (2.95 t/ha). The seed yield of Gepak Kuning and Seulawah were not high, i.e. 2.20 and 1.82 t/ha respectively. The three highly susceptible or susceptible varieties also showed the lowest seed yield, i.e. 0.68 t/ha (Argomulyo), 0.42 t/ha (Grobogan) and 0.99 t/ha (Malabar). The negative correlation was shown between resistance to pest with days to maturity, duration of the reproductive phase, the number of unfilled pods, and weight of 100 seeds. Seed yield also had a negative correlation with duration of reproductive phase and weight of 100 seeds. It indicated that varieties with short duration of reproductive phase and small seed size were preferred by Nezara viridula as food sources. Therefore, these two characters can be used to determine the soybean resistance to Nezara viridula.